2019
DOI: 10.1111/aos.14273
|View full text |Cite
|
Sign up to set email alerts
|

Ganglion cell layer thickening in well‐controlled patients with type 1 diabetes: an early sign for diabetic retinopathy?

Abstract: Purpose: To evaluate early changes in retinal layers using optical coherence tomography (OCT) in patients with long-standing type 1 diabetes (DM1) receiving intensified insulin therapy. Methods: In a cross-sectional case-control study 150 patients with DM1 and 150 age-and sex-matched healthy control participants underwent OCT imaging. Scans of both eyes were analysed for different layers (NFL, GCL (+IPL), INL, outer layer complex (OLC, including OPL, ONL and ELM) and photoreceptors (PR)) in all subfields of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 39 publications
1
11
1
2
Order By: Relevance
“… 47 , 56 For example, our quantification of RGCs assumes that cellular density within a given volume of tissue remains constant and the change in RGCs is accurately reflected by the change in volume. Moreover, as previously mentioned, inner retinal tissue thickening has also been described 53 in diabetic patients, likely due to subtle swelling of the neural tissue. This would make our assumption of constant density unreliable.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“… 47 , 56 For example, our quantification of RGCs assumes that cellular density within a given volume of tissue remains constant and the change in RGCs is accurately reflected by the change in volume. Moreover, as previously mentioned, inner retinal tissue thickening has also been described 53 in diabetic patients, likely due to subtle swelling of the neural tissue. This would make our assumption of constant density unreliable.…”
Section: Discussionmentioning
confidence: 60%
“…The measured impact of these factors on neuronal damage has been variable across different reports. 13 , 21 , 53 , 58 In our study population, the average duration of the disease was short. This was expected from our selection criteria, since patients with type 2 diabetes and no DR are likely to have only been recently diagnosed.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…With OCT, the analysis of single retinal layers thickness showed a slight progressive thinning of the inner retina layers, specifically RNFL, GCL, IPL, and INL and a mild thickening of ORL in diabetic eyes compared to controls, even if a statistically significant difference was not reached. The thinning of inner retina has already been reported, as secondary to increased apoptotic phenomena of the retinal neuronal cells in DM [29,30]. Histopathologic studies have shown that ganglion cells dendrites are the first cellular component damaged in diabetic models, followed by their axons and cellular bodies [31,32].…”
Section: Discussionmentioning
confidence: 87%
“…Fluorescein angiography is a method which accurately locates the sites of leakage of diseased vessels and ischemia zones, and OCT angiography allows us to accurately visualize vascular changes without the need for contrast agents. In addition, there are a number of other methods that allow accurate diagnosis of lesions within the eye at an early stage of their development [21][22][23]. Recently, Chinese authors have presented results of their research on the thickness of choroid, optic disc, and macular thickness in children with type 1 diabetes [24].…”
Section: Cataractmentioning
confidence: 99%